Odpowiedzi

2009-12-01T20:55:39+01:00
W(x) =2x⁴+x³+2x² +2x²+x+2=x²(2x²+x+2)+1(2x²+x+2)=(x²+1)(2x²+x+2)

w(x)=x³-x-12x-12=x(x²-1)-12(x+1)=x(x-1)(x+1)-12(x+1)=(x+1)[(x-1)x-12]
Najlepsza Odpowiedź!
2009-12-01T20:58:11+01:00
W(x)=2x4+x3+4x2+x+2=2x4+x3+2x2+2x2+x+2=x2(2x2+x+2)+(2x2+x+2)=(x2+1)(2x2+x+2)

w(x)=x3-13x-12
pierwiastkiem teog wielomianu takim ze w=0 jest liczba -1
1 0 -13 -12
-1 1 -1 -12 0
w(x)=(x+1)(x2-x-12)
liczymy delte do rownania kwadratowego (@)
@=1-4*1*(-12)=1+48=49 pierwiastek z @=7
x,=(1+7)/2=4
x,,=(1-7)/2=-3
w(x)=(x-+1)(x-4)(x+3)